Detection of ACE Gene SNPs Using rhAmp Genotyping Platform and Their Association with I/D Polymorphism in COVID-19 Patients with Hypertension - Faustine, Ingrid; Malik, Amarila; Andrajati, Retnosari; Wanandi, Septelia Inawati (Indonesian Journal of Pharmacy, 2023)
The high activity of Angiotensin Converting Enzyme (ACE) in patients with hypertension is thought to affect the risk and severity of COVID-19. Insertion/deletion (I/D) and SNP polymorphisms of the ACE gene can affect ACE activity in the Renin-Angiotensin System (RAS). This study aims to identify linkage disequilibrium SNPs rs4331 (A/G), rs4341 (G/C), and rs4343 (G/A) with I/D polymorphisms reported in previous studies and their associations with the severity of COVID-19 with hypertension comorbid. A cross-sectional study in 2021 recruited 95 samples of COVID-19 patients from two regions representing the eastern and western parts of Indonesia. Detection of polymorphisms using rhAmp SNP showed the percentage of genotypes GG, AG, and AA at rs4331 according to genotype II, DI, and DD in polymorphism I/D (57%, 32%, and 11%). In contrast, rs4341 only showed one type of genotype (GG), and 37% of the samples were undetermined at rs4343. Based on the linkage disequilibrium, it is known that rs4331, rs1799752, and rs4343 are in strong LD (D’= 0.97 and 0.99), and rs4331 and rs1799752 can be markers of genes to replace one with another (R2= 0.957). The haplotype analysis showed a significant difference between the residents of western and eastern Indonesia (p = 0.005), whereas this was not the case with hypertension comorbidities and the severity of COVID-19. Seventeen percent of the G-I-G-G haplotypes showed moderate-severe severity, while 15% of the A-D-G-G haplotypes showed mild severity. Therefore, it can be concluded that the high I/D, rs4331, and rs4343 polymorphisms are likely co-inherited and that the G-I-G-G haplotype is associated with moderate-to-severe severity in COVID-19.